PENGARUH STRES TERHADAP DISMINORE PRIMER PADA MAHASISWA KEBIDANAN DI JAKARTA - Rus Martin; Sri Mulyati; Yudhia Fratidhina (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
The complained of pain during the menstrual of woman, the results of respondens in midwifery education is disminore proportion reached 33.1% (42 people). Women who experience disminore up to 51%, do not interfere with the activity or school attendance, 8%. The purpose of this study to determine the effect of stress on pain levels. Samples were selected purposively by the number of 46 people. Processing data through ANOVA test. The results obtained average pain level of 6.70 with SD 1518 students, and the majority of student stress conditions to normal conditions 54.3% (25) and the stress was 17.4% (8) students. The results of the stress test with no influence pain level students (p- 0, 045). These stress conditions can lower the body's resistance so it will be very sensitive to pain, and each individual will be different in response to pain. The result research is suggest all students to get konwledge of management stress in the lessing the paint menstrual.